Selective expression of constitutively activated STAT6 in intestinal epithelial cells promotes differentiation of secretory cells and protection against helminths - Schubart, Christoph; Krljanac, Branislav; Otte, Manuel; Symowski, Cornelia; Martini, Eva; Günther, Claudia; Becker, Christoph; Daniel, Christoph; Vöhringer, David (Mucosal Immunology, 2018)
Intestinal epithelial cells (IECs) constitute an important barrier between host and pathogen. Immune mechanisms that provide protection against gastrointestinal helminths often require IL-4Rα-induced activation of STAT6-regulated genes in IECs. However, it is not known whether STAT6 activation in IECs enhances protective immunity against helminths. Furthermore, the regulation of proliferation and differentiation processes of the intestinal epithelium by IEC-intrinsic STAT6 signaling remains unclear. To address these questions, we generated mice with specific expression of a constitutively active version of STAT6 in IECs. These VillinCre_STAT6vt mice show accumulation of secretory IECs, increased proliferation of IECs and lengthening of the small intestine. They rapidly expelled Nippostrongylus brasiliensis worms even in the absence of T cells. Furthermore, primary infection with Heligmosomoides polygyrus resulted in larval trapping in the submucosa and the fecundity of adult worms was severely impaired. Our results reveal an important IEC-intrinsic role of STAT6-regulated genes for intestinal homeostasis and protective immunity against helminths.
EVALuna2:35396